Risks in Distribution Outsourcing: An Analytical Approach to Mitigation - Bing Tan (Decision Making: Applications in Management and Engineering, 2024)
Many organisations whose primary operations do not involve logistics typically face two strategic choices regarding the management of their logistics activities. The first involves managing logistics internally, referred to as in-house logistics, while the second entails delegating these functions to specialised external providers, thereby allowing the organisation to concentrate on its core competencies. Due to the consider-able benefits associated with outsourcing, numerous companies opt for this approach. However, outsourcing has notable implications for key supply chain functions, particularly in relation to cost efficiency and operational flexibility. In light of these considerations, the present study aims not only to explore the risks linked to logistics outsourcing but also to assess them quantitatively. To this end, the research identifies and evaluates 15 distinct risks. The findings reveal that three specific risks—vulnerability in data protection, the large-scale departure of skilled personnel, and inadequate training of contracted staff—are categorised as high. Corresponding mitigation strategies have been recommended to address these high-priority risks.